Gender based perspectives about organ donation among students in a medical school in North India - Gupta, Rajiv Kumar; Singh, Parveen; Akhtar, Najma; Kumari, Rashmi; Gupta, Chandini; Gupta, Riya (International Journal of Research in Medical Sciences, 2018)
Background: Deaths due to organ failure are reaching alarming numbers mainly due to paucity of organ donation. The medical students who are the future doctors hold promise to alleviate this paucity by willing to register as a donor themselves as well as facilitating cadaver organ donation process. Objective was to assess the perspectives (awareness and attitudes) of medical students regarding organ donation. Methods: The present cross sectional descriptive study was conducted among 280 undergraduates’ students of Government Medical College Jammu, J and K, India. A pretested and self administered 22 item questionnaire was used to collect information on socio-demographic characteristics (5), to assess awareness (11) and attitude (6) about organ donation. Results: Higher proportion of female students were aware about transplantation of human organ act (p<0.05). Awareness about organ donation card was very poor among both the sexes. Only 77.50% of the respondents were aware of the legal age for organ donation. Higher proportion of male students considered themselves to be future organ donor (p<0.05) although both the sexes wanted to be informed more on organ donation. Organ could be wasted (47.14%) was the main barrier among respondents for organ donation. Conclusions: The awareness and attitude among the respondents were found to be non-desirable on many parameters. Authors suggest introduction of a teaching module which should include all aspects of organ donation in medical schools starting from first profession onwards.